Javanese Local Wisdom-Based Corporate Social Responsibility at PT PLN (Persero) UP3 Mojokerto - Singgih Bayu Indra Hermawan; Eka Ananta Sidharta; Endang Sri Andayani (Cita konsultindo, 2023)
The purpose of this study is to explain how the practice and disclosure of Corporate Social Responsibility are based on local culture and local wisdom. This study uses Stakeholder Theory and Enterprise Theory and the approach used in this study is qualitative research using a type of case study approach. A case study is an approach or strategy that